(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In modern second language teaching system the role of pragmatics is huge and considered to be a new approach to include into the teaching process. In language learning process, especially in English language classes, it is common to come across with problems concerning cultural diversity and use of English language in a correct way. However, learners having their pragmatic norms of native language in mind, they miscomprehend language norms of target language, that is likely to lead to overgeneralization of perceived L2 pragmatic norms. The given work deals with the problems of lack of pragmatics in English classes and suggests the design of activities on pragmatics using speech acts.